Watchful waiting? Portuguese approach to otitis media with effusion - Vera-Cruz,Paulo (2021)
Abstract Introduction and objective: Otitis media with effusion (OME) is an important public health problem. Several clinical practice guidelines for diagnosis and treatment of OME are in place, including from the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS). This study aimed to evaluate the clinical practice of OME diagnosis and treatment among the Otolaryngology medical community working in Portugal. Material and methods: A questionnaire was developed based on AAO-HNS guidelines regarding placement of tympanostomy tubes in children. Each directive was transformed into a question, and further questions were added to improve the characterization of the population and its practices. Results: Answers provided agreed with “recommendations” and “recommendations against” enunciated in the guidelines. The exceptions were recommendations regarding the adoption of measures to prevent water from entering the external ear canal of children with tympanostomy tubes and the use of drugs. Questions asked outside guidelines scope revealed that 96.7% of doctors consider children’s age and 49.1% wait for the end of summer when deciding about surgery for tube placement, 68% recommend bathing in beaches, and 21.9% recommend mineral water treatment. Conclusion: These results suggest that Portuguese otolaryngologists act according to the latest international guidelines and consider factors like season, bathing in beaches, and mineral water treatment in surgical or treatment decisions.